The symbolic meaning of ruwatan bumi for youth as successors of tradition in Guci, Tegal - Setiawan, Aditya Fajar; Arsal, Thriwati; Atmaja, Hamdan Tri (JESS (Journal of Educational Social Studies), 2022)
Youth as a measure of cultural integrity is an essential element. Without youth, culture will gradually disappear into the earth. Youths begin to reason by viewing a culture that looks ancient and contains mystical elements (irrational) without seeing or understanding the symbolic meaning of the elements of the Ruwatan Bumi tradition. The development of today's era makes people's understanding of the meaning and symbolic elements of the Ruwatan Bumi tradition begin to blur, especially the youth. This study aims to analyze the implementation of the Ruwatan Bumi procession in Guci Village, the meaning of the youth toward the Ruwatan Bumi tradition in Guci Village, and the social attitudes of youth towards the Ruwatan Bumi tradition. The youth of Guci Village rarely follows the Ruwatan Bumi tradition ceremony. This study uses a qualitative approach, obtaining data through in-depth interviews, documentation, and observation. Validation of data using triangulation from Mils and Huberman. The results show that the implementation of the Ruwatan Bumi tradition is still carried out every year. Ruwatan begins with bathing and slaughtering Mendit goats and continues with Kidungan. Youth interpret Ruwatan Bumi as a ritual, ceremony, entertainment, and thanksgiving.